Twenty-Four-Hour Variation of Intraocular Pressure in Primary Open-Angle Glaucoma Treated with Triple Eye Drops. (3rd May 2017) - Itoh, Yoshinori; Nakamoto, Kenji; Horiguchi, Hiroshi; Ogawa, Shumpei; Noro, Takahiko; Sato, Makoto; Nakano, Tadashi; Tsuneoka, Hiroshi; Yasuda, Noriko
Abstract : Objectives. To evaluate 24-hour intraocular pressure (IOP) variation in patients with primary open-angle glaucoma (POAG) treated with triple eye drops. Subjects and Methods. The IOP was measured in 74 eyes in 74 POAG patients (seated) on triple therapy (PG analogue, β -blocker, carbonic anhydrase inhibitor) at about every 3 hours. Results. The peak IOP was 13.5 ± 3.1 at 1:00, and the trough IOP was at 12.6 ± 2.4 mmHg at 7:00. The IOP at 7:00 was significantly lower than that at 10:00, 1:00, and 3:00 (p < 0.05 ). Based on the time of the peak IOP, we classified the patients into two groups: diurnal (28 eyes) and nocturnal types (37 eyes). There was significant difference at the spherical equivalent between diurnal and nocturnal types (p = 0.014 ). To assess the influence of reflective error, we conducted subanalysis for two groups: high myopic (26 eyes, ≤−6D) and low/nonmyopic (24 eyes, ≥−2D) groups. In the low/nonmyopia group, the IOP was significantly higher at 1:00 and 3:00 than at 13:00, 16:00, and 7: 00 (p < 0.05 ). Conclusion. The mean of IOP elevated outside of clinic hour in the POAG patients on triple therapy. The low/nonmyopia patient should be carefully treated because the IOP of the patients at night elevated significantly.